COMPARATIVE STUDY USING LOW COST ACETIC AND SULFURIC ACIDS ON ROASTING AND PEROXIDE FOR LEACHING PROCESS TO EXTRACT PB FROM GALENA - Wiwik Dahani; Rita Sundari; Subandrio Somali; Irfan Marwanza; Ivetta Ivetta (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2022)
Extraction of heavy metals from mineral concentrate applying leaching acids is a major issue due to simple, fast, and economical process. This article aims to present the application of acetic acid and sulfuric acid for lead (Pb) extraction from galena concentrate applying roasting (600oC and 60 min.) and peroxide oxidant (0.5 M) for 60 min. leaching process. Nowadays, lead has been broadly applied for batteries, besides for PVC tubes, chemicals, paint color, and alloys for joint. The peroxide increases the percentage of Pb extraction. This study shows the effect of acid concentrations (1.0 M, 1.5 M, and 2.0 M), temperatures (30, 50, and 70oC), and stirring speed (200, 400, and 600 rpm) on Pb extraction from galena. A particle size of galena ≤ 200 mesh after roasting has been used for leaching process. AAS has been used to determine Pb concentration in solution after leaching process. This study shows that acetic acid is a better leaching agent rather than sulfuric acid due to lead sulfate precipitation. Optimization result shows leaching with acetic acid achieved 35.64 ppm Pb extraction using 2.0 M acetic acid, 50oC, and stirring speed of 200 rpm. This study used low-cost acids as leaching agent for Pb recovery that can be viewed as a preliminary breakthrough in heavy metal recovery. The simple leaching technique looks promising for future application on heavy metal separation from mining mineral.